Stubble Management Plays a Greater Role than Tillage Practice in Shaping Soil Microbiome Structure and Function - Chang Xu; Ruey Toh; Jishun Li; Yi Zhou; Matthew D. Denton (Agriculture)
Tillage and stubble management play crucial roles in conservation agriculture, exerting a considerable influence on soil properties. This study aims to focus on the gaps in our understanding of how tillage and stubble management interact to affect the taxonomic and functional structure of the soil microbiome. Soil samples were collected from a long-term field trial implementing no tillage (NT) and conventional tillage (CT) with stubble retention and removal. Metagenomic sequencing facilitated the assembly of a gene catalog comprising 4.36 billion non-redundant genes. Stubble management markedly altered both the taxonomic and functional composition of the prokaryotic community, the addition of stubble caused a significant increase in Proteobacteria, but a decrease in Chloroflexi compared with no stubble. The key prokaryotic species and gene functions contributing most to the dissimilarity of the prokaryotic communities between the treatments with and without stubble were identified, including Rhodospirillum sp. Stubble retention increased the availability of carbon resources in the soil, resulting in a higher proportion of genes functional for metabolic activity and plant–pathogen interactions. However, tillage practice did not influence the structure or diversity of the soil prokaryote community. Our findings identify the target microbial species for future isolation, enabling the development of eco-friendly biofertilizers to promote sustainable agriculture.